Partisipasi Masyarakat Lansia Dalam Program Posyandu ILP Kelurahan Laksamana Kecamatan Dumai Kota - Sari, Nurmala; Latip; Suryani, Lili; Wahyuni, Lilis (Jurnal Administrasi Publik dan Pemerintahan, 2024)
The government changed the integrated service post (Posyandu) to Integrated Primary Service (ILP) Posyandu to improve access, quality and coverage of community-based health services. ILP program aims to bring health services closer to the community through a network of primary health facilities such as Community Health Centers, Village Health Posts, and Posyandu. The enthusiasm of the community in participating in the Posyandu ILP activities varies in various regions. Several reports indicate high participation, while in other regions, the level of participation still needs to be improved. The purpose of this paper is to see community participation in participating in the Posyandu ILP Cendrawasih Laksamana Village program. This research is descriptive with a qualitative approach. Data collection was carried out through key informants who were selected purposively or based on certain objectives. Wilcox's opinion regarding the stages of community participation provides an illustration that the lack of involvement of the elderly in various stages of participation, such as providing information, consultation, and joint decision-making, is the main cause of their low interest in participating in the program.